2017
DOI: 10.1002/2017gb005699
|View full text |Cite
|
Sign up to set email alerts
|

Biological and land use controls on the isotopic composition of aquatic carbon in the Upper Mississippi River Basin

Abstract: Riverine ecosystems receive organic matter (OM) from terrestrial sources, internally produce new OM, and biogeochemically cycle and modify organic and inorganic carbon. Major gaps remain in the understanding of the relationships between carbon sources and processing in river systems. Here we synthesize isotopic, elemental, and molecular properties of dissolved organic carbon (DOC), particulate organic carbon (POC), and dissolved inorganic carbon (DIC) in the Upper Mississippi River (UMR) system above Wabasha, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 98 publications
(137 reference statements)
2
30
0
Order By: Relevance
“…However, this application can be complicated by the presence of additional biogeochemical transformations influencing the observed δ 13 C‐DIC values. The influence of CO 2 evasion on δ 13 C‐DIC values has been documented in soils (Amundson et al, ; Cerling et al, ; Davidson, ), larger river systems (Giesler et al, ; Hélie et al, ; Voss et al, ), and headwater streams (Amiotte‐Suchet et al, ; Doctor et al, ; van Geldern et al, ), but it is likely that the patterns in δ 13 C‐DIC values simultaneously reflect a larger range of sources and processes (Campeau, Wallin, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this application can be complicated by the presence of additional biogeochemical transformations influencing the observed δ 13 C‐DIC values. The influence of CO 2 evasion on δ 13 C‐DIC values has been documented in soils (Amundson et al, ; Cerling et al, ; Davidson, ), larger river systems (Giesler et al, ; Hélie et al, ; Voss et al, ), and headwater streams (Amiotte‐Suchet et al, ; Doctor et al, ; van Geldern et al, ), but it is likely that the patterns in δ 13 C‐DIC values simultaneously reflect a larger range of sources and processes (Campeau, Wallin, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Voss et al [41] showed that in-stream processes such as respiration and photosynthesis were primary drivers determining δ 13 C DIC values, and that in-stream signatures were distinct from their source signatures. The discrepancy between the expected and reported δ 13 C DIC values for the RR could be indicative of the importance of in-stream respiration in its warm waters, which causes more negative values through the removal of 13 C from the aquatic carbon pool [25].…”
Section: Sources and Processes Determining Dissolved Inorganic Carbonmentioning
confidence: 99%
“…The MR and RR's relative influences on organic carbon isotopic signatures in the AR should then be closer to a 1:1 mixing ratio. δ 13 C DOC values retain information about terrestrial sources [41], so although the flow of the MR dominates the AR, organic carbon in the AR can be expected to be highly reflective of the organic material that is found in the soils of the RR basin. In a recent study of isotope signatures in the upper MR, Voss et al, [41] revealed that δ 13 C DOC values became more negative with increased forest cover.…”
Section: Differences In Dissolved Organic Carbon Sources Entering the Armentioning
confidence: 99%
See 2 more Smart Citations